On horizonless temperature with an accelerating mirror - Good, Michael R.R.; Yelshibekova, Khalykbek; Chin Ong, Yen (ArXiv, 2017)
A new solution of a unitary moving mirror is found to produce nite energy and emit thermal radiation despite the absence of an acceleration horizon. In the limit that the mirror approaches the speed of light, the model corresponds to a black hole formed from the collapse of a null shell. For speeds less than light, the black hole correspondence, if it exists, is that of a remnant.
Keywords: Black Holes; Field Theories in Lower Dimensions; Research Subject Categories::NATURAL SCIENCES::Physics